Panniculitis: A dermatopathologist's perspective and approach to diagnosis - Parikshaa Gupta; Uma Nahar Saikia; Sandeep Arora; Dipankar De; Bishan Das Radotra (Wolters Kluwer Medknow Publications, 2016)
Panniculitis is the inflammation of subcutaneous fat. It poses a diagnostic challenge, both for the clinician as well as the histopathologist owing to its diverse etiologies, overlapping morphological features, and dynamic nature of the lesions. The standard protocol for histopathologic diagnosis is to examine deep skin biopsies after staining with hematoxylin and eosin. Sometimes, however, special stains are also needed to rule out varied etiologies. A thorough histopathologic examination in conjunction with appropriate clinical details is the key to identify different subtypes of panniculitis. In this review, we discuss the classification of panniculitis with salient histopathologic features of the subtypes in each category. We also present a diagnostic algorithm for arriving at a definitive histopathologic diagnosis of different panniculitis subtypes.